2010
DOI: 10.1080/13803390902806568
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gender and personality on the Conners Continuous Performance Test

Abstract: A total of 91 university community participants were evaluated on the five personality factors (NEO-Five Factor Inventory; NEO-FFI) and with the Conners Continuous Performance Test (CPT). Gender differences for the Conners CPT variables were found such that the men were faster and less variable in their reaction times than the women, and the women were more sensitive in terms of signal detection and conservative in their responses than the men, consistent with the data reported by Conners, Epstein, Angold, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 24 publications
(29 reference statements)
6
13
0
1
Order By: Relevance
“…Subjects with more conservative bias, on the other hand, want to be rather sure that a degraded stimulus is unambiguously a correct target. The present correlational findings are in line with the literature: Burton et al [32] found that neuroticism is negatively correlated with the decision bias β. Furthermore, they also found that in females the bias is negatively correlated with openness: higher scores of openness are associated with more liberal decisions.…”
Section: Discussionsupporting
confidence: 82%
“…Subjects with more conservative bias, on the other hand, want to be rather sure that a degraded stimulus is unambiguously a correct target. The present correlational findings are in line with the literature: Burton et al [32] found that neuroticism is negatively correlated with the decision bias β. Furthermore, they also found that in females the bias is negatively correlated with openness: higher scores of openness are associated with more liberal decisions.…”
Section: Discussionsupporting
confidence: 82%
“…Although some of the effects did not reach significance, together they strongly suggest that, with time on task, constraint was related to relatively higher engagement, reflecting conservative strategies to prevent increased error rates (Burton et al, 2009). Constraint also was related to left RFA, a less pronounced increase in sadness during the task, and higher vigor before and especially after the task.…”
Section: Errorsmentioning
confidence: 85%
“…"Sex differences become more pronounced during the period of adolescence, concomitant with the hormonal changes of puberty, with females being more efficient than males in tasks of selective attention, verbal fluency and conductive reasoning" (Rubia, Hyde, Halari, GIampietro, & Smith, 2010, p. 817). However, Burton et al (2010) found relationships between personality factors and CPT variables in the male and female groups, especially in terms of response style and vigilance.…”
Section: Discussionmentioning
confidence: 98%
“…They found effects of gender, age, and educational level only for Hit RT and detectability (d') scores. Burton et al (2010) used the CCPT and found gender differences on measures of RT, commission errors, and d' and β indices.…”
Section: Introductionmentioning
confidence: 99%